Was It Pneumothorax? A Case Report of a Neonate with Congenital Pulmonary Airway Malformation from Rural Nepal - Paudel, Pradip Kumar; Devkota, Pragya; Devkota, Bibek (Journal of Nepal Paediatric Society, 2022)
Formerly called congenital cystic adenomatoid malformation (CCAM), congenital pulmonary airway malformation (CPAM) is a rare but most common congenital lung malformation that may manifest as an asymptomatic lesion at birth or in later life. The diagnosis may be difficult and is easily confused for pneumothorax often resulting incorrect ICD insertion on an emergency basis, which causes complications and delays accurate diagnosis. We report a case of a neonate, who presented with increasing respiratory distress at birth and hyperlucency in a chest radiograph initially misdiagnosed as pneumothorax and ICD inserted, later correctly diagnosed as CPAM type I with help of a CT chest. This case report is presented to highlight that CPAM is a rare cause of respiratory distress in newborns at birth.